Exosomes Derived From Heat Stroke Cases Carry miRNAs Associated With Inflammation and Coagulation Cascade - Li, Yue; Wen, Qiang; Chen, Huaisheng; Wu, Xinhui; Liu, Bin; Li, Hui; Su, Lei; Tong, Huasheng (Frontiers in Immunology, 2021)
The pathological mechanism of HS is associated with the dysbalanced inflammation and coagulation cascade. The cells-derived circulating extracellular vesicles (EVs) as a novel pathway mediating intercellular communication were evidenced to be associated with immune response and inflammation in critical inflammatory syndromes such as sepsis. Despite previous studies demonstrating that these vesicles contain genetic material related to their biological function, their molecular cargo during heat stroke is relatively unknown. In this study, we evaluated the presence of microRNAs (miRNAs) and messenger RNAs (mRNAs) related to inflammatory response and coagulation cascade in exosomes of patients with heat stroke. Blood samples were collected from 3 patients with heat stroke at ICU admission. Three healthy volunteers were used as control subjects. Exosomes were isolated by ultracentrifugation, their miRNA content was profiled by next generation sequencing and mRNA content was evaluated by qRT-PCR array. As compared with healthy volunteers, exosomes from patients with heat stroke had significant changes in 202 exosomal miRNAs (154 miRNAs upregulated and 48 downregulated). The most upregulated miRNAs included miR-511-3p, miR-122-5p, miR-155-3p, miR-1290 and let7-5p whileas the most downregulated ones included miR-150-3p, 146a-5p and 151a-3p. The GO enrichment by the miRNAs of patients with heat stroke compared with control subjects were related mostly to inflammatory response including T cell activation, B cell receptor signaling, DC chemotaxis and leukocyte migration, and platelet activation and blood coagulation. KEGG pathway analysis determined those identified miRNAs were mainly enriched to the signal transduction pathways namely, T cell receptor signaling pathway, Ras signaling pathway, Chemokine signaling pathway, Platelet activation, and Leukocyte transendothelial migration. These pathways were mainly related to inflammation and hemostasis. Multiple targeted mRNAs associated with the inflammatory response, blood coagulation and platelet activation were further verified in serum exosomes. Exosomes from patients with heat stroke convey miRNAs and mRNAs related to pathogenic pathways, including inflammatory response and coagulation cascade. Exosomes may represent a novel mechanism for intercellular communication during heat stroke.